2012
DOI: 10.1097/pcc.0b013e31823890de
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin

Abstract: Procalcitonin is useful in the diagnosis of bacterial infection after cardiopulmonary bypass. Because procalcitonin kinetics are different in postcardiopulmonary bypass patients, the cutoff to diagnose infection should be different from the normal cutoff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…[ 13 14 ] Consequently, proposed threshold levels for the identification of BI in prior studies have varied widely, from 0.38 ng/mL to 13 ng/mL, and several authors have suggested using different threshold values for different days or time periods. [ 16 17 18 19 ] In the current study, a PCT level of 2 ng/mL was found to be the optimal threshold value for discrimination of infection. Even at this threshold value, PCT is not highly sensitive or specific for infection.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…[ 13 14 ] Consequently, proposed threshold levels for the identification of BI in prior studies have varied widely, from 0.38 ng/mL to 13 ng/mL, and several authors have suggested using different threshold values for different days or time periods. [ 16 17 18 19 ] In the current study, a PCT level of 2 ng/mL was found to be the optimal threshold value for discrimination of infection. Even at this threshold value, PCT is not highly sensitive or specific for infection.…”
Section: Discussionmentioning
confidence: 64%
“…PCT values on POD 1 were higher in the BI group than in the non-BI group without a statistically significant difference. [ 19 ] Similarly, McMaster et al . compared the median PCT on PODs 1-5 of patients with known infection to patients without fever or suspicion of infection after CHS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine white blood cell (WBC) counts with neutrophil counts, platelet counts, CRP, and erythrocyte sedimentation rate (ESR) were collected from all patients presurgery, then on 4 consecutive days postsurgery, and then predischarge from ICU between day 5 and day 7 postsurgery. Although procalcitonin (PCT) was found to be better marker for sepsis evaluation in some studies,[ 10 11 ] it was not included in our study due to unavailability in our center. Intravenous cefuroxime postcardiac surgery was used routinely and continued until removal of chest drains usually between days 2 and 3 postoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that PCT may be useful for screening of bacterial sepsis after CS in children,1,3,4,12,13 but none of these studies focused on the newborn population. In contrast to older children, uninfected and healthy newborns can present higher PCT values during the first days of life, making it difficult to establish a cutoff value for PCT 1416…”
Section: Introductionmentioning
confidence: 99%